Mechanical and anticorrosion efficiency of organic coatings with polyaniline phosphate and polypyrrole phosphate modified pigments - Kalendová, Andréa; Kohl, Miroslav (Wydawnictvo SIGMA-NOT, 2020)
This paper describes the results of a study of the anticorrosion efficiency of composite materials prepared by precipitating conductive polymer salts on the surface of synthesized pigment particles. Specifically, composite pigments with polyaniline phosphate and polypyrrole phosphate were prepared. The novelty consists in testing the anticorrosive properties of composite pigments based on tungsten and molybdate, which have been surface treated with salt conductive polymers. Strontium, zinc and ferric molybdates and tungstates were synthesized and described and then coated with the conductive polymer salts. Twelve composite material samples were prepared and described and paints containing them as pigments were formulated. A solvent-type epoxy-ester resin served as the binder. The volume concentrations of the composite materials in the paint were 1%, 5%, 10% and 15%. The paints were applied to steel panels and the anticorrosion efficiency of the composite pigments was measured in dependence on the conductive polymer salt type and pigment volume concentration. Paint samples containing a commercial zinc phosphate pigment were prepared as reference materials. The physico-mechanical properties of the paints were also measured: the paint films exhibited an outstanding mechanical resistance. The steel panels coated with the paints were subjected to accelerated cyclic corrosion tests, the results point to a very good anticorrosion efficiency of the organic coatings containing the composite particles examined.
Mechanická a antikorozní účinnost organických povlaků s pigmenty modifikovanými polyanilin fosfátem a polypyrol fosfátem
Keywords: organic coating; polyanilin phosphate; polypyrrol phosphate; epoxyester resin; molybdate; tungstate; organický povlak; polyanilin fosfát; polypyrol fosfát; epoxyesterová pryskyřice; molybdenan; wolframan